Maladaptive Emotion Socialization as a Risk Factor for the Development of Negative Urgency and Subsequent Problem Drinking. (25th August 2022) - Atkinson, Emily A; Miller, Leo A; Smith, Gregory T
Abstract: Aims: Negative urgency, which refers to the tendency to act rashly when experiencing intense negative emotions, consistently serves as a robust predictor of problem drinking and other maladaptive behaviors. However, very little is known about the factors that influence the development of negative urgency itself. Although urgency theory suggests that environment and temperament interact to increase risk for the development of urgency, few studies, to date, have examined environmental risk for urgency. Method: In a cross-sectional sample of 518 adults recruited from Amazon Mturk, the current study began the investigation of the role of childhood maladaptive emotion socialization (MES) in risk for negative urgency and the possibility that negative urgency mediates the relationship between MES and problem drinking via self-report measures completed online. Data were analyzed using structural equation modeling. Results: Individual differences in childhood MES, reported retrospectively, did predict increased present-day negative urgency. In addition, results were consistent with the possibility that negative urgency mediates the relationship between MES and problem drinking when considered concurrently with trait negative affect. Conclusions: Successful identification of early environmental predictors of negative urgency may provide useful targets for intervention efforts aimed at reducing or preventing the development of negative urgency and, subsequently, problem drinking. Further longitudinal investigations are needed to better examine these processes as they develop.